Bodyweight Estimation of Anglo Nubian Dairy Goats at Lobi Farm, Pondok Kubang, Central Bengkulu: Estimasi Bobot Badan Kambing Perah Anglo Nubian di Peternakan Lobi Farm, Pondok Kubang, Bengkulu Tengah - Bilyaro, Woki; Endang Sulistyowati; Muhammad dani; Azis, Arif Rahman (BPFP Universitas Bengkulu, 2024)
Dairy goats are small ruminants that have the potential to become fresh milk producers to fulfill the milk needs in Indonesia. Anglo Nubian goats are one type of dairy goat found in Lobi Farm, UMKM Bukit Bengkulu. The purpose of the study was to determine the level of correlation between body measurements, namely body length (PB), chest circumference (LD), and shoulder height (TP) to body weight (BW) of Anglo Nubian goats. A total of 22 Anglo Nubian goats were used in this study. The research data collected were primary data from direct measurements and secondary data. The data analysis used was correlation and multiple linear regression using the R program. The results showed that TP, PB and LD were each positively and significantly correlated with the body weight of Anglo Nubian goats with correlation coefficients of 0.516, O.715, and 0.884, respectively, while together TP, PB and LD were correlated by 0.916. Chest circumference correlated best with body weight when using a single variable. Whereas, the combination of BL and CG was the best and simplest regression model in correlation to body weight of Anglo Nubian goats with the regression equation.